Calcareous Nannoplankton and Planktonic Foraminifera from the Neogene Offshore Northwest Borneo - Shirley E. van Heck (Ikatan Ahli Geologi Indonesia, 2001)
The sediments penetrated by hydrocarbon wells offshore NW Borneo consist mainly of Neogene clastics. Sedimentation rates are very high, resulting in a demand for high-resolution stratigraphy. As a result of often unfavorable environments and poor preservation, age diagnostic planktonic foraminifera and calcareous nannofossils are rare or absent in many wells. Although deepwater deposits are relatively rich in planktonics, compared to other areas the yield and preservation are poor.This paper describes the sequence of events (first and last occurrences) commonly encountered offshore NW Borneo, with indications of the reliability of the observed events.